The Charleston earthquake - Williams, Nannie Elizabeth (My University, 1899)
Introduction: This, the greatest of recent American geologic disasters, occurred in the vicinity of Charleston, South Carolina, August 31st, 1886. The city of Charleston is situated near the coast, and on a narrow strip of land between the two rivers Ashley and Cooper. It is very low in some places and intersected by number of streams. This makes it necessary that much of the city be built on “made” land, a fact which seemed to have something to do with the destructive effects of the earthquake. The great shock of august 31st was preceded for some months by smaller preliminary ones. Early in the summer of 1886, several slight tremors were felt, but did not attract much attention at the time. During the sitting of the United States Court, in Charleston, in the month of June, we are told that there was a decided rattling of the window sashes, which attracted attention and which was thought by a few to be caused by something other than the passing of heavy loads or boiler explosions.
Citation: Williams, Nannie Elizabeth. The Charleston earthquake. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Preliminary Tremors; Great Shock; Direction of Vibrarions; Theses; Manuscripts (documents)